MAIN CHARACTER'S EXPRESSIVE SPEECH ACTS FOUND IN TOM HOOPER'S "THE KING'S SPEECH" - Dwi Wahyuningtyas (Jurnal Bahasa Lingua Scientia, 2022)
An expressive speech act is among parts of speech acts, which is often met in many aspects, including in movies. The main character in